Dynamics of trade of recycled raw materials and the connection with the circular economy - Aurelija Burinskienė; Olga Lingaitienė; Gintarė Byčenkaitė (Discover Sustainability)
Abstract The trade of recycled raw materials is an essential part of the circular economy model of economic development, which contributes to resource efficiency, keeps goods in circulation, and reduces society’s negative environmental impact. Recycling raw materials is particularly relevant for countries with a limited number of natural resources, where the recycling of raw materials significantly impacts the reduction of raw material imports and raw material prices. Recycled raw materials provide significant conservation of primary raw materials. In this paper, the authors used a multistage research methodology to review key variables, identified relationships between trade in recycled raw materials and private investment into recycling, and links between construction and demolition waste recovery and circularity. The authors described the evolution of different types of waste, the volume they generate, and their influence on the trade of recycled raw materials. After applying the Robust least squares method, the authors formed a regression equation and reflected the result in a graph to forecast the trade volume in recycled raw materials in the 27 European Union (EU) countries for 12 years. The paper concludes that the study of the volume of trade in recycled raw materials is a relatively new topic that focuses on recycled raw materials, promotes sustainability and circularity, and conserves natural primary resources. The results of this study show that trade in secondary raw materials (i.e., recycled materials) is an important element of the circular economy and an important environmental and economic policy instrument. This study bridges the gap between sustainability ambitions and practical implementation mechanisms within circular economic systems. The proposed regression model not only enables forecasting of trade volumes but also serves as a strategic tool for policymakers and stakeholders aiming to promote investment and optimize waste recovery systems.